Melaka gastronomy identity towards local tourist satisfactions and its relationship to dissemination behavior / Faizal Mohd Yusof, Nur Akmal Fathiah Che Musa and Nurul Faezah Roshidi - Mohd Yusof, Faizal; Che Musa, Nur Akmal Fathiah; Roshidi, Nurul Faezah (2014)
Gastronomy is a branch of tourism products that attract anyone including tourist and investor that consists of foods, beverages and food cultures. This research focuses on Melaka gastronomy identity towards local tourist satisfactions and its relationship to dissemination behaviour. Based on reviewing previous studies, this study containing three main categories of attributes: (1) foods, (2) beverages, (3) food cultures, and suggested that this attributes can influence towards local tourist satisfactions and its dissemination behaviour. In comparison with other literature, this study focuses its scope to the local tourist rather than an international tourist. Hence, this research looks at the dissemination behaviour of the local tourists towards gastronomy products. The questionnaires were distributed to the Melaka main tourist areas namely Kota Laksamana, Klebang and Bandar Hilir. Using quantitative approaches the experiences of one hundred and fifty local tourists were tapped. Through a series of descriptive and inferential analyses, some useful understandings or analysts on the issues of interest revealed. Finding clearly revealed that local tourist's dissemination behaviour towards foods, beverages and food cultures have positively influenced bythe tourist satisfaction of local tourists. Foods attributes among the most contributors that give the positive impact to the local tourist's satisfactions compared to beverages and food cultures. The results also contribute to the future literature especially in the gastronomy tourism in Malaysia which needs further exploration.